2006
DOI: 10.1191/0269215506cr979oa
|View full text |Cite
|
Sign up to set email alerts
|

Family-centred services in the Netherlands: validating a self-report measure for paediatric service providers

Abstract: The Dutch MPOC-SP is a reliable and valid instrument to measure the family-centredness of service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 27 publications
(13 reference statements)
2
35
2
Order By: Relevance
“…These ICC 2,1 values are similar to those previously described in a rehabilitation setting for the Dutch version of the MPOC-SP. 20 These results indicated that the MPOC-SP scale scores, except that for the 'providing general information' scale, are consistent over time, 19 and thus have good test-retest reliability. The responses to the items in the 'providing general information' scale may be influenced by recent events.…”
Section: Discussionmentioning
confidence: 80%
“…These ICC 2,1 values are similar to those previously described in a rehabilitation setting for the Dutch version of the MPOC-SP. 20 These results indicated that the MPOC-SP scale scores, except that for the 'providing general information' scale, are consistent over time, 19 and thus have good test-retest reliability. The responses to the items in the 'providing general information' scale may be influenced by recent events.…”
Section: Discussionmentioning
confidence: 80%
“…The MPOC-SP is an equivalent questionnaire to measure the perception of service providers of the family-centeredness of care. The MPOC and MPOC-SP have sufficient reliability and validity [51,52]. It takes about 10-15 minutes to complete the MPOC-questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore two future adjustments of the questionnaire are suggested here, which were addressed in related studies [18,22,40]. Firstly, a GYV-20 scale score does not correct for the value adolescents and young adults attribute to certain acts.…”
Section: Discussionmentioning
confidence: 99%
“…In The Netherlands, the MPOC [22] and the MPOC-SP [18] were made available recently, but a valid measure to ask for the adolescent's or young adult's view on the process of care was not available yet. Since one of the official aims for future paediatric rehabilitation in The Netherlands is to pay more attention to youth [23], such a measure has a high clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation